2008
DOI: 10.1061/(asce)1090-0241(2008)134:4(437)
|View full text |Cite
|
Sign up to set email alerts
|

Earth Pressure due to Vibratory Compaction

Abstract: This paper presents experimental data on the variation of lateral earth pressure against a nonyielding retaining wall due to soil filling and vibratory compaction. Air-dry Ottawa sand was placed in five lifts and each lift was compacted to achieve a relative density of 75%. Each compacted lift was 0.3 m thick. The instrumented nonyielding wall facility at National Chiao Tung University in Taiwan was used to investigate the effects of vibratory compaction on the change of stresses at the soil-wall interface. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…As the backfill height increases beyond 0.5 m, the earth pressure significantly increases at the top of the backfill compared to the bottom, due to compaction effort. These results are in good agreement with the experimental results of Chen and Fang [33], which showed higher earth pressure at the top of vibratory compacted model wall compared to the bottom. It can be concluded that the distribution of earth pressure resulted from overconsolidated sand on nonyielding walls is not hydrostatic nor following the traditional jacky's formula.…”
Section: Earth Pressure Distributionsupporting
confidence: 91%
“…As the backfill height increases beyond 0.5 m, the earth pressure significantly increases at the top of the backfill compared to the bottom, due to compaction effort. These results are in good agreement with the experimental results of Chen and Fang [33], which showed higher earth pressure at the top of vibratory compacted model wall compared to the bottom. It can be concluded that the distribution of earth pressure resulted from overconsolidated sand on nonyielding walls is not hydrostatic nor following the traditional jacky's formula.…”
Section: Earth Pressure Distributionsupporting
confidence: 91%
“…When experimental results are given in terms of intervals the average values are generally used. Figure 3 shows variation of lateral earth pressure based on different tests (Chen & Fang, 2008). Chen & Fang (2008) studied variation of lateral earth pressure in a block of sand.…”
Section: Uncertainty In the Diffusion Coefficientmentioning
confidence: 99%
“…At a certain depth, the residual lateral pressure may be high enough to cause passive failure in the soil behind the retaining wall; also, the lateral earth pressure measured near the top of the wall was almost identical to the passive earth pressure estimated by Rankine theory. If the cyclic compacting stress applied on the surface of the backfill exceeded the ultimate bearing capacity of the foundation soil, a shear failure zone would develop in the uppermost layer of soil [3]. The effect of compaction on the lateral earth pressure behind retaining walls can be calculated by various methods.…”
Section: Introductionmentioning
confidence: 99%